Literary and Religious Texts. Second Part - Gadd, Cyril J. (1966)
= texts 124-414; Publications of the Joint Expedition of the British Museum, and of the University Museum, University of Pennsylvania, Philadelphia, to Mesopotamia; Printed by Order of the Trustees of the Two Museums.